Pengaruh Lingkungan Keluarga dan Efikasi Diri terhadap Hasil Belajar Siswa Kelas X Mata Pelajaran Ekonomi di SMA Negeri 6 Kupang - Fransiska Yuliana Ayu; Soleman Do; Saverius Kebabu; Fernando Saragih; Andri Paulus Loe (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2026)
The low learning outcomes of students in economics are influenced by various factors that play a role in both encouraging and improving academic achievement. Therefore, this study aims to analyze the effect of these factors on students’ learning outcomes. The study involved a population of 300 tenth-grade students at SMA Negeri 6 Kupang, with a sample of 100 students selected using a simple random sampling technique. This research employed a quantitative approach with a survey method. The research instrument consisted of 20 statements covering the variables of family environment and self-efficacy, all of which were declared valid and reliable. The results of multiple linear regression analysis indicate that the family environment and self-efficacy have a positive and significant effect on students’ learning outcomes. These findings emphasize the importance of a supportive family environment and strong self-efficacy in improving students’ academic achievement. Therefore, this study recommends collaboration between schools and parents in creating a harmonious learning environment, as well as strengthening students’ self-regulation skills through guidance, extracurricular activities, and continuous mentoring.